Cafeína, fármacos, hormônios e produtos de cuidados pessoais no Rio Palmital - PR - Filippe, Tais Cristina (2018)
A wide variety of products present in the daily life of the population is released into aquatic ecosystems. These products contain compounds of different classes, such as pharmaceuticals, hormones, personal care products, among others. The growing interest in these substances occurs mainly because they may exhibit biological activity at very low concentrations of the order of μg L-1 and ng L-1 . Thus, it was evaluated in the presence and concentration of 20 microcontaminants belonging to different classes (anti-inflammatories, lipid regulators, antimicrobials, antiseptics, sex hormones and caffeine) in the Palmital River, located in the Metropolitan Region of Curitiba. In order to investigate the presence these pollutants, monitoring was carried out over four samplings at seven points on the Palmital River. The collected samples were submitted to extraction in solid phase and analyzed by liquid phase chromatography with diode array detector and gas chromatography tandem mass spectrometry. The validation of the methodology used was based on the standards established by the Agência Nacional de Vigilância Sanitária and the Instituto Nacional de Metrologia. The extraction and quantification method were efficient for the determination of these analytes in water samples. Among the contaminants analyzed, Caffeine was detected in almost 100% of the samples and had the highest concentration (3.58 μg L-1 ). Among the investigated pharmaceutical products, ketoprofen was present in 27 of the 28 analyzed samples, but in lower concentrations (maximum concentration of 0.18 μg L-1 ) than the other drugs; acetylsalicylic acid had the highest concentration (2.31 μg L-1 ) followed by paracetamol (1.28 μg L-1 ). Significant concentrations of hormones were also quantified in the Palmital river, as well as the parabens and triclosan indicating a possible anthropic influence in the aquatic environment studied. It was observed that changes were associated with seasonal variations, and in the drought period (October / 2016 and July / 2017) the concentrations were higher for most of the contaminants analyzed in the Palmital River. With the statistical treatment of the data it was possible to verify the relation between the emerging contaminants studied together with the concentrations of Nammonia and Orthophosphate. The results indicated that the Palmital River presents a great anthropic influence, possibly due to the contribution of domestic effluents from densely populated areas, which have a sewage collection and treatment service that does not serve all households.